ASESMEN PENDIDIKAN AGAMA ISLAM BERBASIS PEMBELAJARAN MENDALAM DI SMA YADIKA SUMEDANG - Asep Mustakim; Indri Kurnia; Susanti Susanti; Fitriyani Kosasih (Hikmah: Journal of Islamic Studies, 2025)
AbstractThis study analyzes deep learning-based assessment practices in Islamic Religious Education at SMA Yadika Sumedang. The study is motivated by the tendency of Islamic Religious Education assessment to remain focused on students’ ability to recall religious content, while meaningful understanding, value reflection, and the application of Islamic teachings are not yet assessed systematically. This research employed a qualitative approach with a case study design. Data were collected through classroom observation, interviews with teachers and students, and analysis of lesson modules and assessment documents. The findings show that Islamic Religious Education assessment has begun to shift from outcome-oriented evaluation toward process-oriented assessment. Teachers used oral questioning, classroom discussion, written tasks, short reflections, and attitude observation to identify students’ understanding. The findings also reveal three levels of student responses: textual, contextual, and reflective. However, the implementation remains transitional because reflective indicators, assessment rubrics, formative feedback, and documentation systems have not been developed operationally. This study proposes the concept of value-depth assessment, which consists of conceptual understanding, value meaning-making, self-reflection, and contextual praxis as key dimensions for assessing deeper religious learning. AbstrakPenelitian ini menganalisis praktik asesmen Pendidikan Agama Islam (PAI) berbasis pembelajaran mendalam di SMA Yadika Sumedang. Kajian ini dilatarbelakangi oleh kecenderungan asesmen PAI yang masih dominan mengukur kemampuan mengingat materi, sementara dimensi pemahaman bermakna, refleksi nilai, dan penerapan ajaran Islam belum sepenuhnya terukur secara sistematis. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Data diperoleh melalui observasi pembelajaran, wawancara dengan guru dan siswa, serta telaah Modul Ajar dan dokumen penilaian. Hasil penelitian menunjukkan bahwa asesmen PAI telah mulai bergerak dari penilaian hasil akhir menuju penilaian proses belajar. Guru menggunakan pertanyaan lisan, diskusi, tugas tertulis, refleksi singkat, dan pengamatan sikap untuk membaca pemahaman siswa. Temuan juga memperlihatkan tiga tingkat respons siswa, yaitu tekstual, kontekstual, dan reflektif. Namun, praktik asesmen masih belum sepenuhnya sistematis karena indikator reflektif, rubrik, umpan balik, dan dokumentasi penilaian belum tersusun secara operasional. Penelitian ini mengusulkan konsep asesmen kedalaman nilai yang mencakup pemahaman konseptual, pemaknaan nilai, refleksi diri, dan praksis kontekstual.